Understanding the evolution process of program source for investigating software authorship and plagiarism - Jeonghoon Ji; Suhyun Park; Gyun Woo; Hwangue Cho (2007 Second International Conference on Digital Information Management, 2007)
This paper addresses the evolution process of program source codes to establish the framework for software authorship identification. Since program code cheating is getting serious in academic institutions, we will be able to apply the software authorship identification tool as a detection tool for code plagiarism. The main contribution of our work is twofold. First, we have devised new asymmetric distance measure to compute the distance of authorship between two different programs. Second, we have proposed an algorithm to construct the evolution tree(hylogenetic tree) for a set of similar program clones. For the experiment we have gathered two set of codes: a set of assignment programs and another program set which have been submitted to the ICPC, an international programming contests. Our experiment showed that our distance measure for program sources has successfully identified the code authorship and has also reliably detected plagiarized programs. This experiment has showed a strong possibility that the proposed construction algorithm for phylogenetic forest can be used to trace the evolution(improving) process of software. This paper shows the confidence of the authorship identification and plagiarism detection can be interchangeably applied for both these purposes in student assignment program domain.